Shape prediction and parameter optimization of single-well retreating horizontal salt cavern for energy storage. (March 2023) - Xiao, Ning; Liang, Weiguo; Yu, Yongjun; Zhang, Shengli; Li, Li
Abstract: The single-well retreating horizontal (SWRH) salt rock energy storage has the advantages of high construction efficiency and low cost. However, there needs to be a unified standard for key parameters such as water injection rate, direction and retreat distance in the SWRH leaching process. To solve such a problem, a multi-field coupling numerical model was established, including flow, concentration, temperature fields, and cavern boundary development. The correctness of the numerical model was verified by physical simulation experiments. Before parameter optimization, evaluation criteria of leaching efficiency, water-saving capacity, salt rock formations utilization, and shape regularity coefficient were proposed. The effects of water injection rate, direction, and retreat distance in the SWRH leaching process were analyzed. The feasibility of using air isolation was discussed to deal with the height limitation of salt rock formation. The results showed that increasing the water injection rate led to higher leaching efficiency, higher utilization of salt rock formations and a more regular cavern shape but consumed more freshwater and energy. An upward injection direction increased the leaching efficiency by 5 %–13 % but reduced the shape regularity coefficient and water-saving capacity by 8.3 %–12.3 % and 50 %–67 % relative to a rightward injection direction. The retreat distances were closely related to water injection rates. After air injection, air isolation increased the dissolution rate near the gas-liquid interface 5.41 times due to the brine concentration near the gas-liquid interface being only 44.34 % before air injection. A variable water injection rate, a rightward water injection direction, a retreating distance matching the maximum water injection rate, and a high-frequency gas isolation adjustment were suggested for the SWRH leaching process. The finding promises a broad prospect for the SWRH salt rock energy storage. Highlights: The single-well retreating horizontal (SWRH) leaching method is introduced. A leaching simulation model is established for SWRH cavern shape prediction. The reliability of the model has been verified by physical simulation experiments. Water injection rate, direction, and retreat distance are optimized by simulations. The feasibility of using air isolation is discussed to control SWRH cavern height.